Viscosity jump in the lower mantle inferred from melting curves of ferropericlase - Jie Deng (Nature Portfolio, 2017)
Viscosity increase in the mantle may cause slab stagnation and plume deflection, but the cause has been unclear. Here, the authors perform experiments showing that the viscosity of ferropericlase increases by 10–100 times from 750 to 1250 km depth indicating a single mechanism for these observations.